Dynamic Characteristics Analysis of a Multi-Pile Wind Turbine Under the Action of Wind–Seismic Coupling - Chaoyang Zheng; Yongtao Wang; Jiahua Weng; Bingxiao Ding; Jianhua Zhong (Energies)
When analyzing the dynamics of wind turbines under the action of wind and ground motion, mass–point models cannot accurately predict the dynamic response of the structure. Additionally, the coupling effect between the pile foundation and the soil affects the vibration characteristics of the wind turbine. In this paper, the dynamic response of a DTU 10 MW wind turbine under the coupling effect of wind and an earthquake is numerically studied through the combined simulation of finite-element software ABAQUS 6.14-4 and OpenFAST v3.0.0. A multi-pile foundation is used as the foundation of the wind turbine structure, and the interaction between the soil and the structure is simulated by using p-y curves in the numerical model. Considering the coupling effect between the blade and the tower as well as the soil–structure coupling effect, this paper systematically investigates the vibration response of the blade–tower coupled structure under dynamic loads. The study shows that: (1) the blade vibration has a significant impact on the tower’s vibration characteristics; (2) the ground motion has varying effects on blades in different positions and will increase the out-of-plane vibration of the blades; (3) the SSI effect has a substantial impact on the out-of-plane vibration of the blade, which may cause the blade to collide with the tower, thus resulting in the failure and damage of the wind turbine structure.